1997
DOI: 10.1002/hep.510250609
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of L-ornithine-L-aspartate infusions in patients with cirrhosis and hepatic encephalopathy: Results of a placebo-controlled, double-blind study

Abstract: prandial venous ammonia concentrations in the OAOne hundred twenty-six patients with cirrhosis, hytreated group showed improvements in comparison perammonemia (ú50 mmol/L), and chronic (persistent) with placebo. In addition, venous fasting blood ammonia hepatic encephalopathy (HE), which developed spontaconcentration (P õ .01), mental state gradation (P õ neously without the existence of known precipitating .001), and PSEI (P õ .01), which includes the mental state factors, were enrolled in a randomized, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
190
0
22

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(217 citation statements)
references
References 35 publications
2
190
0
22
Order By: Relevance
“…[15][16][17] Several treatment modalities that reduce ammonia level have been tried in order to treat this condition, for example, dietary protein manipulation, 18 branched-chain amino acids, 19 L-ornithine L-aspartate, 20 lactulose, 21,22,46 and probiotics. 23 Most of the studies of these treatment modalities have found improvement in psychometry, [19][20][21][22][23] ammonia level, 20,23,24 and cerebral edema. 46 We did not measure ammonia level in our patients; however, we believe that improvement in the MHE in our patients most likely was related to the same mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Several treatment modalities that reduce ammonia level have been tried in order to treat this condition, for example, dietary protein manipulation, 18 branched-chain amino acids, 19 L-ornithine L-aspartate, 20 lactulose, 21,22,46 and probiotics. 23 Most of the studies of these treatment modalities have found improvement in psychometry, [19][20][21][22][23] ammonia level, 20,23,24 and cerebral edema. 46 We did not measure ammonia level in our patients; however, we believe that improvement in the MHE in our patients most likely was related to the same mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Therapeutic interventions that aim to reduce ammonia are also useful in this setting. [18][19][20][21][22][23][24] Most studies have shown improvement in psychomotor functions coupled with a reduction in ammonia level. Improvement in cognitive functions may translate into improvement in HRQOL.…”
mentioning
confidence: 99%
“…8 L-Ornithine-L-aspartate (OA) has been proven to be effective in lowering blood ammonia concentrations in both experimental and human chronic liver failure. [9][10][11] A recent randomized, clinical trial of OA treatment revealed significant reductions in blood ammonia in cirrhotic patients concomitant with a significant improvement of neuropsychiatric symptoms. 10 In view of these findings and of the proposed role of ammonia in the pathogenesis of brain edema in ALF, the present study had 2 aims, namely: 1) to study the efficacy of OA in the prevention of encephalopathy and brain edema in experimental ALF; and 2) to relate this protective effect of OA to altered plasma and cerebrospinal fluid (CSF) concentrations of ammonia and ammonia-related metabolites as well as activities of the ammonia-related enzyme, glutamine synthetase.…”
mentioning
confidence: 99%
“…39 These findings point to L-ornithine-L-aspartate (LOLA) as a promising HE treatment that deserves further evaluation. 42 Metaanalysis of eight randomized controlled trials with 646 patients comparing placebo/no-intervention control, LOLA was significantly more effective in the improvement of HE in the total (RR: 1.49, 95% confidence interval [CI]: 1.10-2.01), overt HE (RR: 1.33, 95% CI: 1.04-1.69). The tolerance ratio, incidence of adverse events, and mortality were not significantly different between LOLA and the placebo/nointervention control.…”
Section: L-ornithine-l-aspartatementioning
confidence: 99%